2005
DOI: 10.1186/1471-2458-5-96
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prevalence and severity of asthma among adolescents in the Caribbean islands of Trinidad and Tobago: results of a nationwide cross-sectional survey

Abstract: Background: Asthma is a growing problem in the Caribbean but the prevalence in most islands is unknown and possible inter-island variation in prevalence has not been determined. A nationwide cross-sectional survey was conducted to compare the prevalence of asthma symptoms among high school students in the two islands of the Republic of Trinidad and Tobago.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 5 publications
0
18
2
Order By: Relevance
“…Using the ISAAC, that same study investigated 5000 adolescents in the two islands of Trinidad and Tobago, and their study revealed that severe asthma occurred more frequently in students from Tobago (6). A quarter of the respondents in the survey from the two islands reported wheezing, and night cough was the commonest reported symptom, occurring in over 35% of respondents (6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the ISAAC, that same study investigated 5000 adolescents in the two islands of Trinidad and Tobago, and their study revealed that severe asthma occurred more frequently in students from Tobago (6). A quarter of the respondents in the survey from the two islands reported wheezing, and night cough was the commonest reported symptom, occurring in over 35% of respondents (6).…”
Section: Discussionmentioning
confidence: 99%
“…A quarter of the respondents in the survey from the two islands reported wheezing, and night cough was the commonest reported symptom, occurring in over 35% of respondents (6). It was found that although self-reported wheeze is common in the Trinidad and Tobago adolescents, there is variation between the two territories, with high school students in the less industrialized Tobago reporting more severe asthma symptoms as well as exercise-induced wheeze (6). Economic parameters and access to healthcare were thought to be potential explanations for the reported results; however, these are similar between the two islands; thus, differences in ethnicity were cited as potential explanations for the findings (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Barbados between admissions to an acute setting increased from 36 to 360 patients per month despite an increase of only 10% in the island's population during that time [3]. Similarly for the one year period 1999 in Trinidad 5.3% of all adult admissions and 23% of pediatric admission to the emergency room were asthma related [4]. As a result acute asthma impacts significantly on emergency facilities.…”
Section: Introductionmentioning
confidence: 99%